1999
DOI: 10.1128/aac.43.12.2925
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characterization of Integrons, Genetic Elements Mediating Multiple-Drug Resistance, in Avian Escherichia coli

Abstract: Antibiotic resistance among avian bacterial isolates is common and is of great concern to the poultry industry. Approximately 36% (n ‫؍‬ 100) of avian, pathogenic Escherichia coli isolates obtained from diseased poultry exhibited multiple-antibiotic resistance to tetracycline, oxytetracycline, streptomycin, sulfonamides, and gentamicin. Clinical avian E. coli isolates were further screened for the presence of markers for class 1 integrons, the integron recombinase intI1 and the quaternary ammonium resistance g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
3
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(131 citation statements)
references
References 57 publications
8
109
3
6
Order By: Relevance
“…Frequent resistance patterns of our E. coli and S. Choleraesuis isolates were resistance to ␤-lactams, aminoglycosides, tetracyclines and sulfonamides, in agreement with previous reports from other countries [2,[17][18][19][20][21][22][23][24]. A previous investigation in Taiwan showed that more than 1400 tons of antimicrobial agents were consumed a year for humans and animals.…”
Section: Discussionsupporting
confidence: 89%
“…Frequent resistance patterns of our E. coli and S. Choleraesuis isolates were resistance to ␤-lactams, aminoglycosides, tetracyclines and sulfonamides, in agreement with previous reports from other countries [2,[17][18][19][20][21][22][23][24]. A previous investigation in Taiwan showed that more than 1400 tons of antimicrobial agents were consumed a year for humans and animals.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that resistance to specific antibiotics, such as streptomycin, continues to be prevalent among E. coli isolates despite the discontinuance of use as therapeutic agents [29]. The high frequency of dihydrostreptomycin resistance might have been caused by the widespread use of dihydrostreptomycin and streptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal and plasmid-borne integrons have been identified as one of the crucial factors for the development of multidrug resistance in Enterobacteriaceae as well as many other bacterial species by harboring and lateral gene transfer of gene cassettes (Bass et al, 1999;Ochman et al, 2000;Roe et al, 2003;Stokes et al, 2001). To date, three distinct classes of resistance integrons have been described with more than 60 different antibiotic resistance genes (Collis et al, 2002;Fluit and Schmitz, 2004;Heir et al, 2004).…”
Section: Molecular Epidemiology Of Resistancementioning
confidence: 95%